Guidance from a Royal College, does it have the force of law?. (January 2013) - Ritchie, Andrew
When a Royal College issues clear guidance on clinical practice, do NHS Trusts throughout the UK have to comply with that and if so how long do the Trusts have to implement the changes? Is cost relevant to the decision? And if a Trust fails to implement the changes necessary to comply with the guidance and patients suffer as a result, will the Trust become liable in law for the injuries and damage caused? These were the issues in a recent clinical negligence claim brought by Mr L against the Mid Essex NHS Trust. Mr L suffered a transient ischaemic attack and attended his general practitioner and later his local A & E department. Neither referred him to the local TIA service. Eleven days later he suffered a massive stroke and is now paralysed down one side.